CHARACTERIZATION OF VIRULENCE FACTORS DISTRIBUTION IN MULTIDRUG RESISTANT PSEUDOMONAS AERUGINOSA ISOLATES RECOVERED FROM A TERTIARY CARE HOSPITAL, SOUTH INDIA - ELLAPPAN KALAIARASAN,; HARISH BELGODE NARASIMHA, (International Journal of Pharma and Bio Sciences, 2016)
Background: Pseudomonas aeruginosa is an opportunistic nosocomial pathogen which causes severe infections in cystic fibrosis and immunocompromised patients. The aim of this study was to investigate the antimicrobial susceptibility patterns and virulence factors in clinical isolates of Pseudomonas aeruginosa. Methodology: A total of 365 Pseudomonas aeruginosa isolates (339, non-mucoid and 26, mucoid) were collected during the study period (January 2014 – March 2015). Antimicrobial susceptibility testing (AST) was carried out using different antimicrobial agents such as ceftazidime, amikacin, gentamicin, ciprofloxacin and meropenem. All the 365 isolates were screened for pyocyanin, biofilm and alginate production. Pyocyanin assay was carried out using chloroform method and biofilm assay was conducted in 96 well microtitre plates. Alginate production was carried out using carbazole method. Results: Meropenem is the most effective antibiotic against mucoid (92% sensitivity) and non-mucoid (78% sensitivity) isolates. Pyocyanin production was detected in 67% of non-mucoid isolates and none of the mucoid isolates showed pyocyanin production. Biofilm formation was observed in 31% of mucoid and 11% of non-mucoid isolates. Alginate production was observed in 96% of mucoid and 61% of non-mucoid isolates. Biofilm formation as well as alginate production ability was found in 23% of mucoid and 8% of non-mucoid isolates. Conclusion: This study sheds light on the prevalence of multidrug resistance and virulence factors in clinical isolates of Pseudomonas aeruginosa. In addition, the strong correlation between mucoid nature and antimicrobial resistance in Pseudomonas aeruginosa was highlighted.